2018
DOI: 10.1186/s12911-018-0663-1
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria decision analysis (MCDA) in health care: a systematic review of the main characteristics and methodological steps

Abstract: BackgroundThe health area is one of the most affected systems on the perspective of decision-making with multiobjectives, thus becoming prone to errors in the final solution, however, multicriteria decision analysis (MDCA) appears as an aid tool for this process decision-making. Therefore,the present study aims to analyze and synthesize articles found in the literature, involing MCDA in health care, evaluating general issues and methodological aspects, structuring them in a single work.MethodsSurveys in the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 88 publications
3
79
0
1
Order By: Relevance
“…They analyzed the trends in MCDA publications in addition to the types of sources and methods used to develop particular parts of the MCDAs. Based on their review, they identified a growing trend in the application of MCDA in the field of health, with great emphasis from the year 2014 (Frazão et al, 2018). This finding is in line with our approach of restricting the timeframe of our research to 2013 and beyond.…”
Section: Discussionsupporting
confidence: 56%
“…They analyzed the trends in MCDA publications in addition to the types of sources and methods used to develop particular parts of the MCDAs. Based on their review, they identified a growing trend in the application of MCDA in the field of health, with great emphasis from the year 2014 (Frazão et al, 2018). This finding is in line with our approach of restricting the timeframe of our research to 2013 and beyond.…”
Section: Discussionsupporting
confidence: 56%
“…The first stage starts following the MCDA application parameters presented by [34], which consists of three basic steps: Definition of the problem, Definition of the alternatives and Definition of the criteria [45,46].…”
Section: First Stepmentioning
confidence: 99%
“…Before selecting and implementing any method for MCDA, one must define the limits of the problem to be addressed, the more accurately the problem is defined, the more precise will be the analysis results [1]. The definition of the problem has happened, mainly, through discussion groups, formed by interdisciplinary teams and based on the knowledge and experience of the decision makers about the problem in question, with the possibility of consulting the relevant literature as well as specialists in the field [5].…”
Section: Multicriteria Decisionmentioning
confidence: 99%
“…The use of MCDA as a method to support the establishment of health care priorities is not new. Some researchers show its growing importance in the health care area [4,2,5,6], especially in the context of public health systems [7,8,9,10]. This is due to the combination of restricted resources and growing demands, which have led decision makers to address this issue more directly than in the past [11].…”
Section: Introductionmentioning
confidence: 99%